Environmental Proxies and Methodological Biases in the Environmental Kuznets Curve. Critiques of the Use of Temperature in the Model Proposed by Erazo-Camacho et al. (2024) - Espejo Ordonio, Diego (2025)
The Environmental Kuznets Curve (EKC) is widely used to examine the relationship between economic growth and environmental degradation. However, its empirical application critically depends on the selection of appropriate indicators. This article presents a methodological critique of the article «Peru's Environmental Kuznets Curve 2010-2020: A Departmental View» written by Erazo-Camacho et al. (2024), which employs average temperature as a proxy for environmental degradation in an econometric model applied to Peru. It is argued that this choice introduces methodological biases that undermine the validity of its conclusions, particularly the claim that an increase in per capita GDP reduces regional temperatures. This conclusion contradicts established scientific literature (IPCC, 2023), which links fossil fuel-based economic growth and extractive expansion to increased greenhouse gas (GHG) emissions. Through a literature review, data analysis, and conceptual discussion, the article proposes that more suitable indicators for the EKC in extractive economies include sectoral CO₂ emissions, deforestation, and water pollution. The study concludes that the use of inadequate proxies not only distorts empirical analysis but also risks leading to flawed environmental policy decisions, misrepresenting the true effects of economic growth on the environment.